The future of ocean governance and capacity development: essays in honor of Elisabeth Mann Borgese (1918-2002) - Werle, Dirk (Brill Nijhoff, 2018)
Front Matter -- The Future of Ocean Governance and Capacity Development /Dirk Werle , Paul R. Boudreau , Mary R. Brooks , Michael J.A. Butler , Anthony Charles , Scott Coffen-Smout , David Griffiths , Ian McAllister , L.McConnell Moira , Ian Porter , Susan J. Rolston and Peter G. Wells -- Perspectives on Ocean Governance -- Capacity Development for Responsible Ocean Governance -- Law of the Sea and Principled Ocean Governance -- Ocean Sciences -- Integrated Coastal and Ocean Management -- Fisheries and Aquaculture -- Ocean Energy -- Maritime Safety and Security -- Maritime Transportation -- Communication and Negotiation -- Looking Ahead: Ocean Governance Challenges in the Twenty-First Century /Dirk Werle , Paul R. Boudreau , Mary R. Brooks , Michael J.A. Butler , Anthony Charles , Scott Coffen-Smout , David Griffiths , Ian McAllister , Moira L. McConnell , Ian Porter , Susan J. Rolston and Peter G. Wells.
Includes index
Keywords: Festschrift; Umweltpolitik; Seevölkerrecht; Meeresökosystem; Mann-Borgese, Elisabeth; Umweltschutz; Meer